La efectividad normativa de los gobiernos regionales en Ecuador: análisis y evaluación - Álvarez Yanza, Karen Abigail (2025)
This scientific article analyzes the regulatory effectiveness of Regional Autonomous Governments in Ecuador, evaluating their feasibility compared to other countries that have implemented similar models, such as Peru and Spain. The central issue is the lack of implementation of regionalization in Ecuador, despite being established in the 2008 Constitution and the Organic Code of Territorial Organization, Autonomy, and Decentralization (COOTAD). The removal and subsequent reinstatement of deadlines for the formation of regions have created a regulatory and administrative void, preventing effective development. A qualitative methodology was used to address this issue, based on a literature review and a deductive approach, analyzing current regulations, reform attempts, and international experiences. The results indicate that, compared to Peru and Spain, Ecuador has not succeeded in establishing a functional framework for regional governments due to a lack of planning, coordination, and political will. The functions assigned to Regional Governments are already fulfilled by other structured and similarly mandated Decentralized Autonomous Governments (COOTAD). In countries like Peru, although regional governments were implemented, they have faced issues of corruption and dependence on the central government, demonstrating that decentralization does not necessarily guarantee better development.